Preparation method of carbon-coated lithium iron phosphate
By combining liquid phase and vapor phase deposition, the problems of poor performance of lithium iron phosphate batteries and uneven carbon coating are solved by high-temperature solid phase method, and the uniformity and high electrical performance of carbon-coated lithium iron phosphate are achieved, which is suitable for the application of lithium-ion batteries.
Patent Information
- Application Number
- CN202510087081.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, lithium iron phosphate batteries prepared by high-temperature solid phase method have poor performance and uneven carbon coating, which affects the performance of lithium-ion batteries.
Carbon-coated lithium iron phosphate was prepared by combining liquid phase and vapor phase deposition. The liquid phase reaction was carried out at a pH of 3.0-5.0 and a temperature of 100-110°C. Then, it reacted with the carbon source gas in a vapor phase deposition furnace to form a uniform carbon coating.
This method simplifies the preparation process, reduces energy consumption, and the obtained carbon-coated lithium iron phosphate has good uniformity, dispersion, high spherical shape, exhibits excellent electrical properties, and improves electrical properties in lithium-ion batteries.
Smart Images

Figure CN119873781A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a method for preparing carbon-coated lithium iron phosphate. Background Art
[0002] Lithium-ion batteries are one of the most commonly used batteries in new energy vehicles. The performance of the positive electrode material directly affects the various performance indicators of lithium-ion batteries and is a key factor restricting the further development of lithium-ion batteries towards high energy, long life and low cost. Lithium iron phosphate (LiFePO4) has become one of the mainstream materials in the power and energy storage market with its outstanding advantages such as higher safety, lower cost and longer life. The high-temperature solid phase method is currently the method used by most companies to prepare lithium iron phosphate, but the lithium iron phosphate crystals obtained by this method are large in size and uneven in phase, which affects the compaction density and electrical properties of lithium iron phosphate.
[0003] Carbon coating is an effective method to improve the electrical properties of lithium iron phosphate. The carbon coating layer can reduce the charge transfer impedance at the interface between lithium iron phosphate and the electrolyte and accelerate the charge transfer process; the carbon coating layer can also limit the growth of lithium iron phosphate grain size and maintain the nano-size. The most widely used carbon coating method is to add an organic or inorganic carbon source during synthesis, and after mixing, the high-temperature solid phase method is also used for high-temperature calcination to obtain carbon-coated lithium iron phosphate (LiFePO4 / C). The advantage of this method is that it is suitable for large-scale industrial production. The disadvantage is that it requires flash drying, converter sintering, ball mill grinding and other steps. The process is complicated, and the mixing may be uneven, which will eventually lead to uneven carbon coating, which will affect the electrical properties of lithium-ion batteries. In addition, poor control of carbon coating will reduce the tap density of the material, increase the volume of the battery, and increase the cost of the battery. Summary of the invention
[0004] In view of the technical problems in the prior art that lithium iron phosphate prepared by a high-temperature solid phase method has poor electrical performance and uneven carbon coating, the present invention provides a method for preparing carbon-coated lithium iron phosphate, in which carbon-coated lithium iron phosphate is prepared by combining liquid phase and vapor phase deposition, and the carbon coating is uniform and has good electrical properties.
[0005] The technical solution of the present invention is as follows: A method for preparing carbon-coated lithium iron phosphate comprises: conducting a liquid phase reaction of an iron salt solution and a lithium salt solution in a reaction system with a pH of 3.0-5.0 and a temperature of 100-110° C. until the slurry color turns green, then keeping the temperature for 2-5 hours, filtering, washing, and drying to prepare lithium iron phosphate; placing the lithium iron phosphate in a vapor deposition furnace, conducting vapor deposition with an introduced carbon source gas at a temperature of 600-800° C., and keeping the temperature for reaction for 10-18 hours to obtain carbon-coated lithium iron phosphate; Wherein, the molar ratio of iron to lithium is 1:2.0-2.6; Phosphoric acid was used to adjust the pH of the reaction system.
[0006] The ionic reaction equation in the liquid phase reaction is as follows: PO4 3- + 3Li + → Li3PO4; 3Fe 2+ +2PO4 3- +8H2O → Fe3(PO4)2·8H2O; Fe3(PO4)2·8H2O + Li3PO4→ 3LiFePO4+ 8H2O.
[0007] Furthermore, the iron salt is selected from one of FeCl2·4H2O, FeSO4·7H2O, Fe(CH3COO)2 and Fe(H2PO4)2.
[0008] Furthermore, the lithium salt is selected from one of LiH2PO4, LiOH·H2O and CH3COOLi.
[0009] Furthermore, the solvent in the iron salt solution and the lithium salt solution is water or an organic solvent, the concentration of the iron salt solution is 0.8-1.5 mol / L, and the concentration of the lithium salt solution is 1.0-3.0 mol / L.
[0010] Furthermore, the feeding method of the liquid phase reaction is to pump liquid B into liquid A, and then add phosphoric acid to adjust the pH; liquid A is one of an iron salt solution and a lithium salt solution, and liquid B is the other of the iron salt solution and the lithium salt solution.
[0011] Furthermore, when liquid B is pumped into liquid A, the temperature of the reaction system is 30-100° C., and the pumping speed of liquid B is 1.0-1.2 L / h.
[0012] Furthermore, the carbon source gas is selected from one or more of methane, ethane, propane and butane.
[0013] Furthermore, the carbon source gas has an inlet flow rate of 10-40 mL / min.
[0014] The beneficial effects of the present invention are: The preparation method provided by the present invention does not require flash drying, converter sintering and other steps when preparing lithium iron phosphate, which reduces energy consumption and simplifies the steps; compared with the traditional high-temperature solid phase method, the lithium iron phosphate is directly coated with carbon by chemical vapor deposition, which saves sanding, spraying and other processes, shortens the preparation cycle, reduces energy consumption, and the prepared carbon-coated lithium iron phosphate has good uniformity and dispersibility, high sphericity, and exhibits excellent electrical properties. In addition, the lithium iron phosphate prepared by the preparation method also contains a small amount of Li3PO4, which can also improve the electrical properties of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0016] Figure 1 This is a scanning electron microscope photograph of the lithium iron phosphate of Example 2 at 1000 times magnification.
[0017] Figure 2 This is a scanning electron microscope photograph of the lithium iron phosphate of Example 2 at 3000 times magnification.
[0018] Figure 3 This is a scanning electron microscope photograph of the lithium iron phosphate of Example 2 at a magnification of 10,000.
[0019] Figure 4 This is a scanning electron microscope photograph of the lithium iron phosphate of Example 2 at a magnification of 30,000.
[0020] Figure 5 This is a scanning electron microscope photograph of the carbon-coated lithium iron phosphate of Example 2 at 1000 magnification.
[0021] Figure 6 This is a scanning electron microscope photograph of the carbon-coated lithium iron phosphate of Example 2 at 3000 magnification.
[0022] Figure 7 This is a scanning electron microscope photograph of the carbon-coated lithium iron phosphate of Example 2 at a magnification of 10,000.
[0023] Figure 8 This is a scanning electron microscope photograph of the carbon-coated lithium iron phosphate of Example 2 at a magnification of 30,000.
[0024] Fig. 9 This is a scanning electron microscope photograph of the lithium iron phosphate of Comparative Example 1.
[0025] Fig.10 This is a scanning electron microscope photograph of the lithium iron phosphate of Comparative Example 2.
[0026] Fig.11 This is a scanning electron microscope photograph of the lithium iron phosphate of Comparative Example 3.
[0027] Fig.12 This is a scanning electron microscope photograph of the lithium iron phosphate of Comparative Example 4.
[0028] Fig.13 This is the XRD diagram of the lithium iron phosphate of Example 1.
[0029] Fig.14This is the charge and discharge curve of the button cell sample prepared from the carbon-coated lithium iron phosphate of Example 1 at 0.1C. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0031] Example 1 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeCl2·4H2O and LiH2PO4 were weighed in a molar ratio of 1:2.0. FeCl2·4H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 0.8 mol / L. LiH2PO4 was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 1.0 mol / L. (2) Add iron salt solution into the reactor as the base liquid, set the temperature of the reaction system to 30°C, pump the lithium salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 3.0, raise the temperature to 100°C for liquid phase reaction until the slurry turns green, and keep the temperature for 2h. Then filter and wash the product, put it into an oven, and bake it at 80°C for 12h to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder is placed in a vapor deposition furnace, the furnace temperature is raised to 600°C at a heating rate of 2°C / min, and then methane gas is introduced into the furnace at a flow rate of 10 mL / min. The reaction is kept at this temperature for 18 hours to obtain carbon-coated lithium iron phosphate.
[0032] Example 2 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0033] Experimental Example 3 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) Fe(CH3COO)2 and CH3COOLi were weighed in a molar ratio of 1:2.4. Fe(CH3COO)2 was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.0 mol / L. CH3COOLi was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 2.0 mol / L. (2) Add iron salt solution into the reactor as the base liquid, set the temperature of the reaction system to 80°C, pump the lithium salt solution into the reactor at a rate of 1.0 L / h, add phosphoric acid to adjust the pH of the reaction system to 4.5, raise the temperature to 100°C for liquid phase reaction until the slurry turns green, and keep the temperature for 4 hours. Then filter and wash the product, put it into an oven, and bake it at 100°C for 8 hours to obtain powdered lithium iron phosphate. (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 750°C at a heating rate of 6°C / min. Then, propane gas was introduced into the furnace at a flow rate of 30 mL / min. The reaction was kept at this temperature for 12 hours to obtain carbon-coated lithium iron phosphate.
[0034] Example 4 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) Fe(H2PO4)2 and CH3COOLi were weighed in a molar ratio of 1:2.6. Fe(H2PO4)2 was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.2 mol / L. CH3COOLi was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 1.5 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 100°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 5.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 5 hours. Then filter and wash the product, put it into an oven, and bake it at 110°C for 6 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder is placed in a vapor deposition furnace, the furnace temperature is raised to 800°C at a heating rate of 8°C / min, and then butane gas is introduced into the furnace at a flow rate of 40 mL / min. The reaction is kept at this temperature for 10 hours to obtain carbon-coated lithium iron phosphate.
[0035] Comparative Example 1 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:3.0. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0036] Comparative Example 2 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 6.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0037] Comparative Example 3 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 50°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0038] Comparative Example 4 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) The temperature in the reactor was set to 50°C, and the iron salt solution and the lithium salt solution were pumped into the reactor in parallel at a rate of 1.0 L / h. Phosphoric acid was added to adjust the pH of the reaction system to 4.0, and the temperature was raised to 100°C for liquid phase reaction until the slurry turned green. The temperature was then kept for 3 hours, and the product was filtered and washed, placed in an oven, and dried at 90°C for 10 hours to obtain powdered lithium iron phosphate. (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0039] Comparative Example 5 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 550°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0040] Comparative Example 6 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 900°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0041] Comparative Example 7 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 20 mL / min. The reaction was kept at this temperature for 3 hours to obtain carbon-coated lithium iron phosphate.
[0042] Comparative Example 8 A method for preparing carbon-coated lithium iron phosphate comprises the following steps: (1) FeSO4·7H2O and LiOH·H2O were weighed in a molar ratio of 1:2.2. FeSO4·7H2O was dissolved in ultrapure water to obtain an iron salt solution with a concentration of 1.5 mol / L. LiOH·H2O was dissolved in ultrapure water to obtain a lithium salt solution with a concentration of 3.0 mol / L. (2) Add lithium salt solution into the reactor as the base liquid, set the temperature of the reaction system to 50°C, pump the iron salt solution into the reactor at a rate of 1.0L / h, add phosphoric acid to adjust the pH of the reaction system to 4.0, raise the temperature to 100°C to carry out liquid phase reaction until the slurry turns green, and keep the temperature for 3 hours. Then filter and wash the product, put it into an oven, and bake it at 90°C for 10 hours to obtain powdered lithium iron phosphate; (3) The lithium iron phosphate powder was placed in a vapor deposition furnace, and the furnace temperature was raised to 650°C at a heating rate of 4°C / min. Then, ethane gas was introduced into the furnace at a flow rate of 100 mL / min. The reaction was kept at this temperature for 16 hours to obtain carbon-coated lithium iron phosphate.
[0043] Experimental Example 1 (1) Scanning electron microscope detection The lithium iron phosphate and carbon-coated lithium iron phosphate prepared in Examples 1-4 were examined by scanning electron microscope (SEM). The SEM images of the lithium iron phosphate of Example 2 at different magnifications are shown in FIG. Figure 1-4 As shown, the SEM images of the carbon-coated lithium iron phosphate of Example 2 at different magnifications are as follows Figure 5-8 The lithium iron phosphate prepared in Comparative Examples 1-4 was examined by scanning electron microscopy, and the SEM image is shown as follows: Figure 9-12 shown.
[0044] As can be seen from the figure, the lithium iron phosphate not coated with carbon in Example 2 presents a long strip of particles, and the particles are relatively large; while the carbon-coated lithium iron phosphate in Example 2 has good consistency and dispersion, and a high sphericity, indicating that the lithium iron phosphate particles are uniformly coated with carbon, which can effectively improve the conductivity. Similar results were also detected in other examples (not shown). The product of Comparative Example 1 includes long strips of lithium iron phosphate and granular Li3PO4. The products of Comparative Examples 2-4 include different amounts of long strips of Fe3(PO4)2·8H2O.
[0045] (2) X-ray diffraction test The lithium iron phosphate prepared in Examples 1-4 and Comparative Examples 1-4 was subjected to X-ray diffraction (XRD) test. The test results are shown in Table 1. The XRD pattern of the lithium iron phosphate in Example 1 is shown in Fig.13 shown.
[0046] Table 1 X-ray diffraction test results
[0047] It can be seen from the data in Table 1 that the Li3PO4 content of Examples 1-4 is between 1.8% and 2.1%, which is relatively low, while the Li3PO4 content of Comparative Example 1 is 10.1%, which is relatively high. Fig.13 The red line in the middle represents the detection of LiFe(PO4), and the blue line represents the detection of Li3PO4, indicating that the lithium iron phosphate prepared by the liquid phase method provided by the present invention also contains a small amount of Li3PO4, with a content between 1.8% and 2.1%.
[0048] (3) Impurity detection The carbon-coated lithium iron phosphate prepared in Examples 1-4 and Comparative Examples 1-4 was tested for impurities, and the results are shown in Table 2.
[0049] Table 2 Impurity content test results of carbon-coated lithium iron phosphate (ppm)
[0050] (4) Performance testing The carbon-coated lithium iron phosphate prepared in Examples 1-4 and Comparative Examples 1-8 were used to prepare button cell samples, respectively, and their compaction density and electrical properties were tested. The test results are shown in Table 3. The charge and discharge curves of the button cell samples prepared from the carbon-coated lithium iron phosphate in Example 1 at 0.1C are shown in Table 3. Fig.14 shown.
[0051] As can be seen from Table 3, the button cell samples prepared from the carbon-coated lithium iron phosphate of Examples 1-4 have high compaction density and good electrical properties. Compared with Example 2, the amount of LiOH·H2O added in Comparative Example 1 when preparing the carbon-coated lithium iron phosphate is too much, and the electrical properties of the button cell samples prepared are poor. The reason for this is that the content of Li3PO4 synthesized in the liquid phase process affects the conductivity. A small amount of Li3PO4 has a positive effect on the conductivity, while a large proportion of Li3PO4 will have a negative effect on the conductivity. Compared with Example 2, the pH of the liquid phase reaction in Comparative Example 2 when preparing carbon-coated lithium iron phosphate is higher. It can be seen from Table 2 that the impurity content of Comparative Example 2 is significantly higher than that of Example 2. It can be seen from Table 3 that the electrical performance of the button battery sample prepared from carbon-coated lithium iron phosphate in Comparative Example 2 is significantly inferior to that of Example 2. The reason for this is that there are usually some impurities in the iron salt raw material. When preparing carbon-coated lithium iron phosphate, the excessively high pH of the liquid phase reaction will cause the impurity ions to precipitate together with the ferrous ions in the reaction system, thereby causing the impurity ions to block the transmission path of lithium ions, reducing their transmission rate and seriously affecting the electrical performance of the carbon-coated lithium iron phosphate. Compared with Example 2, the liquid phase reaction temperature in Comparative Example 3 when preparing carbon-coated lithium iron phosphate is too low. There is a difference in the order of adding iron salt and lithium salt when preparing carbon-coated lithium iron phosphate in Comparative Example 4. From the SEM image ( Figure 11-12 ) and X-ray diffraction test results show that the products of Comparative Examples 3 and 4 are mostly long strips of Fe3(PO4)2·8H2O, which fail to meet the conditions for synthesizing lithium iron phosphate and have poor electrical performance test results. Compared with Example 2, the reaction temperature of the lithium iron phosphate in Comparative Examples 5 and 6 is not suitable during the vapor deposition operation, and the obtained carbon-coated lithium iron phosphate has poor purity and contains more impurities, resulting in poor electrical performance of the prepared button battery. Compared with Example 2, the lithium iron phosphate in Comparative Example 7 has too short a holding time during the vapor deposition operation, and the lithium iron phosphate in Comparative Example 8 has too fast a ventilation flow rate during the vapor deposition operation, both of which will lead to incomplete vapor deposition reaction, thereby affecting the quality of the carbon-coated lithium iron phosphate and the electrical performance of the button battery samples.
[0052] Table 3 Compacted density and electrical performance test results of button battery samples
[0053] Although the present invention has been described in detail with reference to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person of ordinary skill in the art may easily think of changes or substitutions within the technical scope disclosed by the present invention, and these shall be within the scope of protection of the present invention.
Claims
1. A method for preparing carbon-coated lithium iron phosphate, characterized in that: The iron salt solution and the lithium salt solution are subjected to a liquid phase reaction in a reaction system with a pH of 3.0-5.0 and a temperature of 100-110° C. until the slurry color turns green, and then the reaction is kept warm for 2-5 hours, filtered, washed, and dried to obtain lithium iron phosphate; the lithium iron phosphate is placed in a vapor deposition furnace, vapor deposited with a carbon source gas at a temperature of 600-800° C., and the reaction is kept warm for 10-18 hours to obtain carbon-coated lithium iron phosphate; Wherein, the molar ratio of iron to lithium is 1:2.0-2.6; Phosphoric acid was used to adjust the pH of the reaction system.
2. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The iron salt is selected from one of FeCl2·4H2O, FeSO4·7H2O, Fe(CH3COO)2 and Fe(H2PO4)2.
3. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The lithium salt is selected from one of LiH2PO4, LiOH·H2O and CH3COOLi.
4. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The solvent in the iron salt solution and the lithium salt solution is water or an organic solvent, the concentration of the iron salt solution is 0.8-1.5 mol / L, and the concentration of the lithium salt solution is 1.0-3.0 mol / L.
5. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The feeding method of the liquid phase reaction is to pump liquid B into liquid A, and then add phosphoric acid to adjust the pH; liquid A is one of the iron salt solution and the lithium salt solution, and liquid B is the other of the iron salt solution and the lithium salt solution.
6. A method for preparing carbon-coated lithium iron phosphate according to claim 5, characterized in that: When liquid B is pumped into liquid A, the temperature of the reaction system is 30-100°C, and the pumping speed of liquid B is 1.0-1.2 L / h.
7. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The carbon source gas is selected from one or more of methane, ethane, propane and butane.
8. The method for preparing carbon-coated lithium iron phosphate according to claim 1, characterized in that: The flow rate of the carbon source gas is 10-40 mL / min.
Citation Information
Cited By
Preparation method and application of lithium iron phosphate positive electrode material
CN121247766A
Preparation method and application of lithium iron phosphate positive electrode material
CN121247766B